(untitled) (INNOVATIVE ECONOMY, 2020)
Ianioglo A.I. PROBLEMS OF PROVIDING ECONOMIC SECURITY AT THE ENTERPRISE Purpose. The aim of the article is substantiation of the choice of indicators for assessing the economic security of the enterprise and measures to strengthen it. Methodology of research. General scientific and special methods are used in the process of research: in determining the methodological provisions; when forming the system of economic security of the enterprise; when substantiating the main directions of strengthening the economic security of the enterprise and in choosing indicators for assessing the economic security of the enterprise. Findings. The important methodological positions of forming the system of economic security of the enterprise are determined. It is established that the system of economic security of an enterprise should: be complex and ensure the security of its main functional components; formed at the stage of enterprise creation and is not an addition, but part of the enterprise. The method of determining the level of economic security of enterprises, which is based on the analysis of indicators characterizing the main spheres of life of the enterprise, is proposed. The basic directions for strengthening of economic safety of the enterprise for each of functional components are outlined. It is substantiated that providing of economic safety of the enterprises is the basis of sustainable development of business and economy as a whole. It is established that achievement of economic security is possible only with the systematic and integrated approach to its organization. Originality. The comprehensive system of providing economic security of the enterprise, which is a set of means, methods and measures aimed at ensuring the qualitative protection of the interests of the economic entity from external and internal factors that can lead to economic losses, is substantiated in the article. Practical value. The obtained research results are the basis of sustainable business development and the economy as a whole. Key words: economic security system of enterprise; economic safety; planning; preventive measures; reactive measures; development; functional components.